ACTIVITY OF CAMELLIA SINENSIS (GREEN TEA) AGAINST TROPHOZOITE AND CYSTIC FORMS OF ACANTHAMOEBA CASTELLANII IN VITRO - Fakae, Lenu B. (2022)
Acanthamoeba castellanii is a free-living unicellular protozoan, which causes acanthamoebiasis clinically seen as granulomatous amoebic encephalitis (GAE) of the brain and Acanthamoeba keratitis (AK) of the eyes. The conclusive effective treatment for these diseases is yet to be determined. This work focused on investigating the amoebicidal and cysticidal effect of Camellia sinensis by subjecting A. castellanii forms to serial concentrations of C. sinensis brews, solvent extract and their bioactive components. From the brew studies, serial concentrations of 25% - 100%(v/v) of C. sinensis brews exhibited a dose-dependent inhibition of trophozoite replication. A similar dose-dependent activity was observed with the exposure of A. castellanii to serial concentrations of 156.25µg/mL - 5000 µg/mL of C. sinensis solvent extract. Ultrastructural alterations in C. sinensis-treated A. castellanii was investigated with electron microscopy studies which revealed loss of cellular membrane integrity of trophozoites and destruction of cysts. These results were corroborated with light microscopy evaluations. Cytotoxicity analysis of C. sinensis against mammalian host cells revealed that C. sinensis exhibited low cytotoxic effects on primary corneal stromal cells and immortalizedhuman corneal epithelial cells (iHCE-2s), with high toxicity to Madin-Darby Canine Kidney cells (MDCKs). Evaluation of the C. sinensis chemical components revealed that epigallocatechin gallate (EGCG) and caffeine exhibited dose-dependent anti-acanthamoebic activity by inhibiting trophozoite replication within the concentrations of 3.125µM - 200µM, and also inhibited encystation alongside theobromine. Proteomic analysis of C. sinensis treated trophozoites showed inhibition of 14-3-3 protein sigma and Keratin type I cytoskeletal 10, while TPI, TrxRases and alpha-enolase inhibited trophozoites replication by inhibition protein and cellulose synthesis. These inhibitions were confirmed by the lack of amide I and II band peaks expression in the treated trophozoites by Fourier-transform infrared spectroscopy (FTIR) analysis. Taken together, these results demonstrated that C. sinensis possess antiacanthamoebic capability making it a potential novel compound which can be further investigated for anti-acanthamoebic drug production.